All-Solution-Processed Van der Waals Heterostructures for Wafer-Scale Electronics - Kim, Jihyun; Rhee, Dongjoon; Song, Okin; Kim, Miju; Kwon, Yong Hyun; Lim, Dong Un; Kim, In Soo; Mazanek, Vlastimil; Valdman, Lukas; Sofer, Zdenek; Cho, Jeong Ho; Kang, Joohoon (WILEY-V C H VERLAG GMBH, 2022)
2D van der Waals (vdW) materials have been considered as potential building blocks for use in fundamental elements of electronic and optoelectronic devices, such as electrodes, channels, and dielectrics, because of their diverse and remarkable electrical properties. Furthermore, two or more building blocks of different electronic types can be stacked vertically to generate vdW heterostructures with desired electrical behaviors. However, such fundamental approaches cannot directly be applied practically because of issues such as precise alignment/positioning and large-quantity material production. Here, these limitations are overcome and wafer-scale vdW heterostructures are demonstrated by exploiting the lateral and vertical assembly of solution-processed 2D vdW materials. The high exfoliation yield of the molecular intercalation-assisted approach enables the production of micrometer-sized nanosheets in large quantities and its lateral assembly in a wafer-scale via vdW interactions. Subsequently, the laterally assembled vdW thin-films are vertically assembled to demonstrate various electronic device applications, such as transistors and photodetectors. Furthermore, multidimensional vdW heterostructures are demonstrated by integrating 1D carbon nanotubes as a p-type semiconductor to fabricate p-n diodes and complementary logic gates. Finally, electronic devices are fabricated via inkjet printing as a lithography-free manner based on the stable nanomaterial dispersions.